Novel TRAPPC2 mutation in a boy with X‐linked spondylo‐epiphyseal dysplasia tarda. Issue 6 (December 2014) - Adachi, Hiroyuki; Takahashi, Ikuko; Takahashi, Tsutomu
Abstract X‐linked spondylo‐epiphyseal dysplasia tarda (SEDT) is an X‐linked recessive, late‐onset, progressive skeletal disorder characterized by mild‐to‐moderate short‐trunked short stature. X‐linked SEDT is caused by mutations in the gene TRAPPC2, which is located on chromosome Xp22. In the present study, we identified a novel splice‐site mutation, c.93+1G>A, in TRAPPC2 in a 9‐year‐old Japanese patient who had X‐linked SEDT and no family history of the disease. On reverse transcription–polymerase chain reaction, the mutation resulted in a 4 bp frame‐shift insertion between exon 3 and exon 4. The present case highlights the importance of genetic analysis for confirmatory diagnosis of X‐linked SEDT, especially in cases without a positive family history.